Wybrane narzędzia do pomiaru rezyliencji (resilience) wśród dzieci i młodzieŜy - Junik, Wioletta (Studia Edukacyjne, 2020)
The interest in research in resilience among children and adolescents from risk groups is rising. Resilience is a multifactorial process of positive adaptation during which risk factors are reduced or compensated by protective factors. The measure of resilience requires research tools which satisfy certain psychometric standards. Many tools which satisfy these requirements already exist in the world; some are already used in many different cultures. There is a deficiency of resilience measuring instruments in our country. No local ones have been created and not many foreign have been adapted in Poland. That is the reason this article presents characteristics and psychometric properties of a few selected scales used to measure resilience and resiliency of children and adolescents. The selection of the tools has been done with use of Google Scholar Database, EBSCO Database and on the grounds of analysis of foreign resilience tool reviews.